APLIKASI RFID SEBAGAI PENGAMAN PINTU MASUK - Harsono, Budi; Liman, Johansah; Djohan, Nani (Teknik dan Ilmu Komputer, 2012)
This paperÃÂ will discussÃÂ the securityÃÂ entranceÃÂ systemÃÂ withÃÂ RFIDÃÂ as anÃÂ identificationÃÂ and detectionÃÂ of theÃÂ personnel whoÃÂ willÃÂ access theÃÂ doorÃÂ ofÃÂ everyÃÂ roomÃÂ that has beenÃÂ fittedÃÂ withÃÂ RFIDÃÂ systems.ÃÂ RFIDÃÂ or RadioÃÂ Frequency IdentificationÃÂ Detection is theÃÂ process of identifyingÃÂ a person orÃÂ object usingÃÂ radioÃÂ frequencyÃÂ transmission.ÃÂ RFID securityÃÂ systemÃÂ was applied to theÃÂ doorÃÂ in the neighborhoodÃÂ Ukrida.ÃÂ Factor ofÃÂ safety,ÃÂ automation,ÃÂ andÃÂ time efficiencyÃÂ is consideredÃÂ in this study.ÃÂ ÃÂ Keywords: pengaman pintu masuk, mikrokontroler, RFID